A 21st Century Warming Threshold for Sustained Greenland Ice Sheet Mass Loss. Issue 5 (6th March 2021) - Noël, B.; van Kampenhout, L.; Lenaerts, J. T. M.; van de Berg, W. J.; van den Broeke, M. R.
Abstract: Under anticipated future warming, the Greenland ice sheet (GrIS) will pass a threshold when meltwater runoff exceeds the accumulation of snow, resulting in a negative surface mass balance (SMB < 0) and sustained mass loss. Here, we dynamically and statistically downscale the outputs of an Earth system model to 1 km resolution to infer that a Greenland near‐surface atmospheric warming of 4.5 ± 0.3°C—relative to preindustrial—is required for GrIS SMB to become persistently negative. Climate models from CMIP5 and CMIP6 translate this regional temperature change to a global warming threshold of 2.7 ± 0.2°C. Under a high‐end warming scenario, this threshold may be reached around 2055, while for a strong mitigation scenario it will likely not be passed. Depending on the emissions scenario taken, our method estimates 6–13 cm sea level rise from GrIS SMB by the year 2100. Plain Language Summary: Under continued climate warming, the Greenland ice sheet will pass a threshold if summertime meltwater runoff outweighs winter snowfall, resulting in sustained surface mass loss. Here, we project climate model data onto a 1 km resolution grid to show that the ice sheet will likely pass this threshold for a 4.5°C Greenland atmospheric warming relative to preindustrial (1850–1899), equivalent to a 2.7°C global warming. Using additional model projections under high, middle and low emission scenarios, we find that the surface mass loss threshold could be passed in the mid‐21st century under high‐end warming scenarios, but likely not for strong mitigation (low emissions) ones. The same method can be used to estimate sea level rise from Greenland surface mass loss, which yields 6–13 cm in the year 2100, dependent on future emissions. Key Points: Greenland surface mass balance is projected at 1 km using dynamical and statistical downscaling The surface mass balance becomes negative for a regional warming of 4.5 ± 0.3°C, compared to preindustrial, and 2.7 ± 0.2°C globally For a fully grounded Greenland ice sheet, this warming would represent the threshold for sustained mass loss